The Impact of Inflammatory Bowel Diseases and Related Medications on COVID-19 Severity and Outcome: A Tertiary Referral Center Experience from Turkey - Er, Ramazan Erdem; Duman, Serkan; Bodakçı, Emin; Yarcı, Büşra; Soykan, Arif İrfan and Törüner, Murat (Turkish Journal of Gastroenterology, 2022)
Background: Coronavirus disease-2019 has become a serious pandemic, and still remains a risk despite vaccines that have been devel- oped. Among inflammatory bowel disease patients old age, inflammatory bowel disease activation, the existence of the comorbid dis- ease, and using steroids are known risk factors for severe coronavirus disease-2019. But there are different data for drugs other than corticosteroids used. The aims of the study are to evaluate the prevalence and risk factors of severe coronavirus disease-2019 and the effect of inflammatory bowel disease drugs on severe coronavirus disease-2019. Methods: In this study among 1195 inflammatory bowel disease patients, 130 patients who were found to be positive for severe acute respiratory syndrome coronavirus-2 between March 2020 and May 2021 were evaluated. Patients were divided into 3 groups as mild, moderate, and severe coronavirus disease-2019. Results: Among 130 patients, 91 (70%) had mild, 16 (12.3%) had moderate, and 23 (17.7%) had severe coronavirus disease-2019. Being 60 years of age or older (P = .009), having at least 1 comorbid disease (P = .002), and having active inflammatory bowel disease (P = .001) were factors that increased the risk for severe coronavirus disease-2019. The use of mesalazine (P = .35), biologic agents (P = .23), and corticosteroids (P = .42) did not increase the risk of severe coronavirus disease-2019. The use of azathioprine seemed to decrease the risk of severe disease with univariate regression analysis however the significance disappeared with multivariate analysis. Conclusion: Older age, active inflammatory bowel disease, and existence of at least 1 comorbid disease are risk factors for severe coro- navirus disease-2019. However, drugs used in inflammatory bowel disease management do not increase the risk of severe coronavirus disease-2019. But due to the small number of patients, it is difficult to reach a definite conclusion about corticosteroids. Cite this article as: Er RE, Duman S, Bodakçı E, Yarcı B, Soykan İ, Törüner M. The impact of inflammatory bowel diseases and related medications on COVID-19 severity and outcome: A tertiary referral center experience from turkey. Turk J Gastroenterol. 2022;33(12):1025-1032.